Experimental identification of LED compact thermal model element values. (July 2018) - Janicki, Marcin; Torzewicz, Tomasz; Samson, Agnieszka; Raszkowski, Tomasz; Napieralski, Andrzej
Abstract: This paper discusses, based on a practical example, the problem of power LED thermal modelling. The precise determination of thermal resistance is crucial for accurate computation of junction temperature, which influences both device lifetime and reliability as well as its operating parameters. Here, diode heating curves are recorded at different levels of dissipated power and in various cooling conditions. Moreover, the devices are soldered to the substrate in different ways, what renders possible the determination of their junction-to-case thermal resistances. For each case, an adequate compact thermal model is generated using the Network Identification by Deconvolution method and validated against the measurements. Highlights: LED R jc can be identified by repeating experiments with disconnected thermal pad. It is possible to generate RC CTMs containing information on physical structure. Simple RC Cauer CTMs provide excellent dynamic simulation accuracy.